Ester-Linked Crystalline Covalent Organic Frameworks - Zhao, Chenfei; Lyu, Hao; Ji, Zhe; Zhu, Chenhui; Yaghi, Omar M (Journal of the American Chemical Society, 2020)
Ester-linked, crystalline, porous covalent organic frameworks (COFs) have been synthesized and structurally characterized. Transesterification reactions between ditopic 2-pyridinyl aromatic carboxylates and tri- or tetratopic phenols gave the corresponding ester-linked COFs. They crystallize as 2D structures in kgm (COF-119) and hcb (COF-120, 121, 122) topologies with surface areas of up to 2092 m2/g. Notably, crystalline COF-122 comprises edges spanning over 10 phenylene units, an aspect that had only been achieved in metal–organic frameworks. This work expands the scope of reticular chemistry to include, for the first time, crystalline ester-linked COFs related to common polyesters.